Kyrgyz Republic : Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for New Three-Year PRGF Arrangement. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility on the Kyrgyz Republic highlights the economic developments and policies. To ensure that the external debt ratios fall, the program introduces a new indicative target for concessional public borrowing. Low inflation and strong productivity growth to contain unit labor costs are crucial to set up favorable conditions for nongold exports. The key to boost productivity is higher private investment, and the program focuses on improving the investment climate.